Navigating an auto guided vehicle using rotary encoders and proportional controller - Lee, Sung How; Kim, Seng Chia (UTHM Publisher, 2017)
Auto Guided Vehicle (AGV) is commonly used in industry to reduce labour cost and to improve the productivity. A few programmable devices are combined in an AGV to optimize the usage of time and energy. AGV is widely used to transport goods and materials from one place to another place. For the first generation of AGV was used the track to guide the AGV but it was not flexible enough. This study investigates an alternative to control an AGV using two rotary encoders and proportional controller. Arduino Mega 2560 was used as a microcontroller to receive and process the signals from the rotary encoders. Logic controller and proportional controller were implemented to control the AGV, respectively. The coefficient of proportional controller was optimized to improve the performance of the AGV during navigation process. Findings show that AGV with the proportional controller with coefficient 1.5 achieved the best performance during the navigation process.